Diagnosis of the cavo-hepato-atrial pathway in Budd-Chiari syndrome by ultrasonography - GAI, YONG-HAO (D.A. Spandidos, 2014)
The aim of this study was to investigate the ultrasonic features of the cavo-hepato-atrial pathway in Budd-Chiari syndrome (BCS), by which blood is drained from the occluded inferior vena cava (IVC) to the right atrium via hepatic veins. Ultrasonograms from 11 patients with BCS with cavo-hepato-atrial pathways were retrospectively studied. Doppler ultrasound was used to observe the direction of the flow and measure the velocity of the blood-draining vessels. Blood flow in the draining vessels and the collaterals was shown as blue, red or bicolored depending on whether the flow direction was away from the transducer, towards the transducer or both. For measurement, the Doppler angle between the axis of the Doppler beam and that of the vein examined was always <60°. Ultrasonography was performed 1–2 weeks prior to digital subtraction angiography (DSA). All patients were confirmed by DSA. Membranous and segmental occlusions of IVCs were observed in seven and four cases, respectively. Blood flow from the IVC reversed to the hepatic/accessory hepatic vein, continued through the dilated intrahepatic collaterals, onward to the other hepatic vein and finally to the right atrium. The majority of the inlets (8/11) of hepatic veins above the occlusion were narrow compared with the dilated distant parts of the lumens. Accelerated blood flow in the inlets was detected in all patients regardless of the luminal diameter. In conclusion, the results from the present study suggest that the unusual cavo-hepato-atrial pathway can be diagnosed reliably by ultrasonography, which may be useful for clinical management.